Refleksi Mahasiswa dalam Berkeadaban Digital melalui ChatGPT - Yuntafaul 'Amala; Muhammad Thohir; Viola Eva Reditiya; Nabila Intan Permata Sari (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2023)
ChatGPT is an artificial intelligence-based machine technology developed by OpenAI. It is trained to simulate human conversation by answering questions and interacting on various topics. This research adopts a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. This study aims to enable technology users, especially students, to understand patterns of digital ethics through ChatGPT in the Islamic educational environment. The research will conduct an in-depth analysis of student reflections on digital ethics through ChatGPT in Islamic Education classes. As students are agents of change, they need to understand patterns of digital ethics through ChatGPT in the Islamic educational environment. The research findings indicate that indicators of digital ethical patterns include respecting privacy and data security, avoiding the spread of illegal or harmful content, respecting ethical communication, being aware of the limitations of ChatGPT, and avoiding system misuse. ChatGPT in Islamic religious education can bring positive benefits and support responsible digital ethics development by considering ethics and morality in digital ethics.